2013
DOI: 10.1021/am401668y
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic TiO2–Polymer Nanocomposite Surface with UV-Induced Reversible Wettability and Self-Cleaning Properties

Abstract: Multifunctional superhydrophobic nanocomposite surfaces based on photocatalytic materials, such as fluorosilane modified TiO2, have generated significant research interest. However, there are two challenges to forming such multifunctional surfaces with stable superhydrophobic properties: the photocatalytic oxidation of the hydrophobic functional groups, which leads to the permanent loss of superhydrophobicity, as well as the photoinduced reversible hydrolysis of the catalytic particle surface. Herein, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(114 citation statements)
references
References 72 publications
0
112
0
Order By: Relevance
“…Nowadays, being used as inorganic additive into polymers has attracted much more attention [3][4][5]. The addition of nano-TiO 2 into polymers can not only improve the UV resistance [6] and mechanical properties [7], but also endows some functional properties, such as photocatalytic antibacterial [8,9] and photocatalytic self-cleaning [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, being used as inorganic additive into polymers has attracted much more attention [3][4][5]. The addition of nano-TiO 2 into polymers can not only improve the UV resistance [6] and mechanical properties [7], but also endows some functional properties, such as photocatalytic antibacterial [8,9] and photocatalytic self-cleaning [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This technique, because of its different applications, has attracted researchers' attention that focused on controlled wetting properties (Wang et al, 2014b;Li et al, 2013b;Xu et al, 2013b;Zhang et al, 2013a;Crick et al, 2012). This is a 'smart coatings' which has the ability to switch from time to time to hydrophilic and hydrophobic surfaces by light irradiating under specific wavelength (Wooh et al, 2014;Nandan et al, 2015).…”
Section: Photo-controlled Wettingmentioning
confidence: 99%
“…hydrophobic functional groups, which leads to the permanent loss of superhydrophobicity, as well as the photoinduced reversible hydrolysis of the catalytic particle surface under UV irradiation, rendering to hydrophilicity. [37,38] To investigate the photoinduced wetting conversion and the stability of (IL/TiO 2 ) n nanocomposites, we irradiated the [C 12 mim]Br/TiO 2 ) 13 films with UV light at 365 nm for 2 hrs. The experimental results showed that the CAs became to be about 10 o (Fig.…”
Section: Page 13 Of 29mentioning
confidence: 99%